Innovation in Civics Learning to Strengthen National Values Through Digital Pianica Music in Elementary Students - Cahyanisam, Clarista; Kumalasari, Indah; Wijayanto, Wasis (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2025)
Introduction/Main Objectives: This study aims to describe the process and impact of innovative learning of Pancasila and Citizenship Education (PPKn) through digital music media using the song